Abiraterone acetate and prednisone in metastatic castration-resistant prostate cancer: a real-world retrospective study in China - Liu, Min; Yan, Jiaqing; Le, Kaidi; Li, Ying; Xing, Nianzeng; Li, Guohui (Frontiers in Endocrinology, 2023)
Background This research work was aimed at evaluating the incidence and risk factors of adverse events (AEs) occurring in patients treated with abiraterone acetate (AA) and prednisone (PDN) outside clinical trials. These associations were assessed regarding the survival outcomes. Methods The study included 191 patients aged ≥18 years of confirmed metastatic castration-resistant prostate cancer (mCRPC) between March 2017 and April 2022. AE incidences were descriptively summarized from the whole cohort. Baseline characteristics, safety (treatment-emergent AEs and severe AEs), and efficacy [progression-free survival (PFS)] were analyzed. Multi-variable Cox proportional hazards models were employed to assess the factors linked with PFS. Results Overall, the median PFS was 17.16 months (range, 0.5–57.58). Patient baseline prostate-specific antigen (PSA) ≧̸10 ng/ml (p = 0.000), multiple organ metastasis (p = 0.007), hypertension (p = 0.004), and coronary heart disease (p = 0.004) were associated with worse PFS; however, radiotherapy (p = 0.028) was linked to better PFS at univariate analysis in the overall cohort. Baseline multiple organ metastasis, hypertension, and radiotherapy remained statistically significant in multivariable models (p = 0.007, p= 0.005, and p = 0.011, respectively).Incidence of AEs showed increased bilirubin (BIL) (55/191 patients, 28.8%) followed by increased alanine aminotransferase/aspartate aminotransferase (ALT/AST) (48/191 patients, 25.09%). The most common grade 3 AEs were increased ALT (3/191, 1.57%) followed by elevated BIL, hypercholesterolemia, and hypokalemia. Anemia had shorter PFS. There were no unexpected AEs in any patient. Conclusion AA is effective and tolerated in asymptomatic or slightly symptomatic mCRPC in “real-life” setting. The survival outcomes are influenced by multiple organ metastasis, hypertension, and radiotherapy.